2014
DOI: 10.1080/03075079.2014.927850
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of Chinese and Australian university students' attitudes towards plagiarism

Abstract: Student plagiarism is a growing problem within Australian universities and abroad. Potentially exacerbating this situation, research indicates that students' attitudes toward plagiarism are typically more permissive and lenient than the policies of their tertiary institutions. There has been suggestion that this is especially so in Asian countries relative to Western countries; however, very little research has sought to empirically validate this suggestion. Moreover, existing research in this area has typical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
46
1
12

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(66 citation statements)
references
References 23 publications
(22 reference statements)
7
46
1
12
Order By: Relevance
“…They may regard compilation of authoritative fragments and quotations, rather than original contributions, as their principal task. Students coming from South Asia or East Asia, and parts of Africa, are generally seen as inheritors of ideologies of sharing and originality quite at odds with those that enforce individual, independent creation (Wong 2013;Ehrich et al 2014;Heckler and Forde 2015).…”
Section: Authorshipmentioning
confidence: 99%
“…They may regard compilation of authoritative fragments and quotations, rather than original contributions, as their principal task. Students coming from South Asia or East Asia, and parts of Africa, are generally seen as inheritors of ideologies of sharing and originality quite at odds with those that enforce individual, independent creation (Wong 2013;Ehrich et al 2014;Heckler and Forde 2015).…”
Section: Authorshipmentioning
confidence: 99%
“…Likewise, a survey of Australian and Chinese undergraduates concluded that Australians are more negative toward plagiarism (31). Although cultural, linguistic and psychological factors determine the behavior of plagiarists, the lack of institutional anti-plagiarism policies is believed to play a more important role (32).…”
Section: Plagiarism In the Context Of Educationmentioning
confidence: 99%
“…Undeniably, the upward trend for plagiarism among non-English speaking countries is also emerging. Researches have shown that this trend is becoming prevalent in Asian countries too (Ehrich, et al, 2014). Albeit studies in Asian countries, particularly in Malaysia are limited, Smith (2007), Iberahim, et al, (2013), Ting (2013, Mah and Ting (2013), Musa and Ting (2013);Ting, Musa and Mah (2014), Jansz and Sari (2015), Cheah (2015), Razali et al (2016), and Bava Harji, Chetty, Ismail and Letchumanan (2016) have provided evidence for plagiarism being equally rampant in non-English speaking countries.…”
Section: Literature Reviewmentioning
confidence: 99%